Ethiopia national dairy forum brings all the actors together - International Livestock Research Institute (International Livestock Research Institute, 2010)
Speaking at the opening of the National dairy forum on 23 November 2010, Agricultural counselor at the Netherlands Embassy, Geert Westenbrink said that he was pleased to see participation by all the private sector, non-governmental and international organizations in the meeting.